(untitled) (Research, Society and Development, 2021)
The government’s relentless attempt to minimize the scarcity of inappropriate homes in the country, designed Brazilian housing programs that employ mass and low-cost construction with the aim of supporting the largest number of families, most of whom do not have access to a complete home. However, an imposition to produce the largest number of residential units with available capital does not constitute a better living condition for the target families and, consequently, a non-reduction of the housing parameter in the cities. In order to understand such circumstances, involved in social housing, research is used with the intention of analyzing housing complexes in order to identify adversities and proposed proposals that aim to produce significant improvements in buildings, urbanization and their insertion in cities. In light of this, the present study sought to validate the efficiency of post-occupation assessment in housing estates through a literature review of a qualitative nature, based on studies developed by the Institute of Applied Economic Research exposing positive and negative questions regarding the theory and applicability of analysis, concluding that the Post-Occupancy Analysis is efficient in studies aimed at entrepreneurship for social housing, due to its opinion, which seen the user’s point of view and the performance of the construction, reaching relevant results.